The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3126/jnphyssoc.v8i3.50729
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Linear Accelerator Output Constancy and Overall Performance Using the PTW Quickcheckwebline

Abstract: Daily morning quality assurance (QA) for all available beams using conventional phantom measures only output and beam quality. PTW QUICKCHECKwebline (PTW QCw) is a compact movable light-weight dosimetry equipment used for daily QA, capable of measuring flatness, symmetry, beam quality and output constancy of a given beam in a single exposure. The purpose of this study was to analyze and monitor the output constancy of a medical linear accelerator using PTW QCw and assess the overall performance of the PTW QCw.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Nyaichyai et al, (2022) [ 8 ] verified the suitability of PTW Quickcheck device for routine quality assurance of the linac for output, energy, flatness and symmetry. Nicewonger et al, (2019) [ 9 ] found the PTW Quick check device to be a suitable tool for daily testing quantitatively and efficient solution qualitatively.…”
Section: Methodsmentioning
confidence: 99%
“…Nyaichyai et al, (2022) [ 8 ] verified the suitability of PTW Quickcheck device for routine quality assurance of the linac for output, energy, flatness and symmetry. Nicewonger et al, (2019) [ 9 ] found the PTW Quick check device to be a suitable tool for daily testing quantitatively and efficient solution qualitatively.…”
Section: Methodsmentioning
confidence: 99%